Highly sensitive detection of daminozide using terahertz metamaterial sensors - Mao, Hanping; Du, Xiaoxue; Yan, Yuting; Zhang, Xiaodong; Ma, Guoxin; Wang, Yafei; Liu, Yong; Wang, Bin; Yang, Xiaoyue; Shi, Qiang (International Journal of Agricultural and Biological Engineering, 2022)
In order to solve the problems of low sensitivity and complex sample pretreatment in traditional detection, a method was proposed in this study to detect daminozide using terahertz combined with a metamaterial sensor, which enables real-time and label-free molecular detection with high sensitivity. The correlation between the transmission frequency shift and absorbance of daminozide solution at different concentrations was analyzed. The simulation and experimental results showed that this metamaterial sensor could achieve highly sensitive sensing of daminozide solutions at 0.05 mg/L. The maximum quality factor (Qmax) of the two peaks could reach 5.78 and 13.05, and the maximum figure of merit (FOM) of the two peaks can reach 0.82 and 1.72. The maximum sensitivity of two resonance peaks reached 38.148 GHz/(mg∙L) and 133.516 GHz/(mg∙L) when the concentration of daminozide in the solution was 2000 mg/L. There was an obvious positive correlation between the transmission and transmission, frequency shift and frequency shift, and absorbance and absorbance of the resonance peak of daminozide solutions. Therefore, this platform not only opens up new possibilities for the microanalysis of the chemical composition of substances in solutions but also provides a valuable reference for the design of other metamaterial-based sensors in the field of food safety.Keywords: Terahertz time-domain spectroscopy, plant growth regulator, detection, metamaterialDOI: 10.25165/j.ijabe.20221506.7600Citation: Mao H P, Du X X, Yan Y T, Zhang X D, Ma G X, Wang Y F, et al. Highly sensitive detection of daminozide using terahertz metamaterial sensors. Int J Agric & Biol Eng, 2022; 15(6): 180–188.